2021
DOI: 10.1007/s10965-021-02674-z
|View full text |Cite
|
Sign up to set email alerts
|

In situ chemical synthesis and characterization of PAN/clay nanocomposite for potential removal of Pb+2 ions from aqueous media

Abstract: A green synthesis of polymer clay nanocomposites (PCNs) was carried out by in situ polymerization for their potential in order to remove the heavy metal from aqueous solution. At first stage, cloisite was functionalized using Vinyl Triethoxy Silane (VTES) to generate radicals on its surface. After functionalization, the monomer was grafted at these functional sites. The grafting was induced by varying initiator ratio (1.0 2.0 and 3. 0wt %). The maximum grafting of 78% was obtained with 2.0%wt initiator. To enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
1
1
0
Order By: Relevance
“…Malayoglu [191] reported a decrease in BET surface area of chitosan/montmorillonite nanocomposite attributing it to compacting in clay's interlayers, of the chitosan molecules thereby blocking nitrogen passage. is research agreed with Batool et al [196] that the average diameter of the pores of the nanocomposites involved was higher compared to the respective non-composited…”
Section: Ermogravimetric Analysissupporting
confidence: 90%
See 1 more Smart Citation
“…Malayoglu [191] reported a decrease in BET surface area of chitosan/montmorillonite nanocomposite attributing it to compacting in clay's interlayers, of the chitosan molecules thereby blocking nitrogen passage. is research agreed with Batool et al [196] that the average diameter of the pores of the nanocomposites involved was higher compared to the respective non-composited…”
Section: Ermogravimetric Analysissupporting
confidence: 90%
“…is was attributed to the loading of the magnetizing Fe 3 O 4 nanoparticles. Batool et al [196] reported similar findings for pore volume when analyzing a polyacrylonitrile/cloisite nanocomposite. Malayoglu [191] reported a decrease in BET surface area of chitosan/montmorillonite nanocomposite attributing it to compacting in clay's interlayers, of the chitosan molecules thereby blocking nitrogen passage.…”
Section: Ermogravimetric Analysismentioning
confidence: 60%